2020
DOI: 10.1002/cre2.291
|View full text |Cite
|
Sign up to set email alerts
|

Recording of diagnoses in public primary oral health care in a retrospective longitudinal observational study in a Finnish town: Underrepresentation of periodontitis diagnoses

Abstract: Objectives This study investigates which oral diagnoses public primary dental care dentists record. Methods An observational register‐based retrospective follow‐up study was performed in the public primary oral health care of a Finnish town after the dentists were advised to mark the diagnoses in their practices. The rate of recorded diagnoses resulting from visits to the public primary care dentists was studied. The assessed diagnoses were recorded with the 10th revision of the International Classification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…With the secondary use of EHR data, there is a need for validation of phenotypes, such as bruxism, to ensure that the codes match diagnoses. Furthermore, while earlier studies show validation analysis between SB in population based samples [ 27 ], in our analysis we did not perform separate validation with chart data but relied on the earlier observations and clinical recommendations. This approach may induce heterogeneity in our analysis that we cannot directly measure in the scope of our own analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the secondary use of EHR data, there is a need for validation of phenotypes, such as bruxism, to ensure that the codes match diagnoses. Furthermore, while earlier studies show validation analysis between SB in population based samples [ 27 ], in our analysis we did not perform separate validation with chart data but relied on the earlier observations and clinical recommendations. This approach may induce heterogeneity in our analysis that we cannot directly measure in the scope of our own analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the International Classification of Diseases (ICD), 10th revision, by the World Health Organization [ 26 ], bruxism is listed under F45.8 “Other Somatoform Disorders.” The adoption of F45.8 code as the code used to denote bruxism in Finland has been implicated also in a recent study and shown to be diagnosed often by Finnish dentists [ 27 ]. To identify individuals with probable SB we extracted ICD-10 codes F45.8 “Other Somatoform Disorders” and G47.8 “Other Sleep Disorders”—another ICD-10 code adopted more recently for SB diagnosis in Finland—from hospital and primary care registries.…”
Section: Methodsmentioning
confidence: 99%
“…A global analysis showed that oral diseases were considered endemic, representing a total of 3.9 billion people worldwide, among whom caries accounts for 35% of cases, despite it being an avoidable disease in comparison with other dental pathologies. For example, severe periodontitis occupies 6th place in the ranking of oral diseases, followed by oral cancer in 11th place and tooth loss in 36th place [12,13].…”
Section: Introductionmentioning
confidence: 99%